Kebijakan Berwawasan Kependudukan dan Peningkatan Kualitas Sumber Daya Manusia - Mahara Sintong Tampubolon (Universitas Negeri Medan, 2014)
In the modern era, population problems considered as one of the important thing which should be solved seriously by government agencies through ‘human-welfare’ based policy regarding population for contributing to minimize the population problem and di-rectly for successing development. That is why in the context of developmental policy, residents must be considered as subject, not as object of development. The population based policy must immediately formulated as guidelines for directing development implemen-tation comprehensively and synergy in producing human resources which able for global competition. Synergycity population based policy with quality of human resources, requiring quality education as a systematic method for improving Indonesian people by several quality such as life skills, personal skills including self awareness and thinking skills, and social skills, academic skills, and vocational skills.